2021
DOI: 10.7759/cureus.18018
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the American Diabetes Association’s Diabetes Risk Test in a Saudi Arabian Population

Abstract: The prevalence of type 2 diabetes (T2D) is growing worldwide. This study aimed to assess the sensitivity and specificity of the American Diabetes Association (ADA) and the United States Centers for Disease Control and Prevention's diabetes risk test in identifying Saudi Arabian patients at risk of developing T2D. MethodsWe conducted a one-month cross-sectional study that included patients older than 18 years who visited primary care facilities for any health concern in Riyadh City, Saudi Arabia. We used the Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
2
7
0
5
Order By: Relevance
“…The current investigation unveiled a strong correlation between gestational diabetes and an elevated susceptibility to DM. This is consistent with the findings of Aldayel et al (13) who demonstrated that women with a previous history of gestational diabetes are at a greater risk of acquiring type 2 diabetes compared to those without such a history, particularly if they don't make beneficial changes to their diet & lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…The current investigation unveiled a strong correlation between gestational diabetes and an elevated susceptibility to DM. This is consistent with the findings of Aldayel et al (13) who demonstrated that women with a previous history of gestational diabetes are at a greater risk of acquiring type 2 diabetes compared to those without such a history, particularly if they don't make beneficial changes to their diet & lifestyle.…”
Section: Discussionsupporting
confidence: 92%
“…Twenty‐four diagnostic trials were assessed for risk of bias and suitability according to the QUADAS‐2 evaluation form. Thirteen 24,26,28,31,35–40,43,45,48 (54.2%) of the 24 studies were judged to be at unclear risk of bias, six 25,29,34,44,46,47 (25%) at high risk of bias, and five 27,30,41,42,49 (20.8%) at low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen 24,26,28,31,[35][36][37][38][39][40]43,45,48 (54.2%) of the 24 studies were judged to be at unclear risk of bias, six 25,29,34,44,46,47 (25%) at high risk of bias, and five 27,30,41,42,49 The study population as a family practice population.…”
Section: Risk Of Bias and Assessment Of Applicabilitymentioning
confidence: 99%
“…9 Another study in Saudi Arabia showed that the results of this screening indicated that these individuals had a high risk of developing DM. 7 A history of pregnancy with diabetes mellitus has a prevalence ratio of 1.12. These results are in line with previous research which stated that gestational diabetes mellitus increases the risk of developing DMT2 compared to other variables.…”
Section: Discussionmentioning
confidence: 99%